Swabian Maultaschen: No Show and a Lot of Substance - Kopf, Petra (Petits Propos Culinaires, 2015)
This article looks at maultaschen which, together with spaetzle, are probably among the best-known regional specialities of the German federal state of Baden-Württemberg. Not only are they an essential part of everyday cuisine, they are considered to be a ‘modern soul food’ as well as a symbol of regional identity. The article looks at how their contemporary popularity was achieved through the confluence of various socio-economic, political and cultural changes during the last century.